Micronucleus Investigation in Buccal Mucosal Cells of Young Waterpipe Tobacco Smokers in Tehran - Sepideh Arbabi Bidgoli; Sepideh Jafari (Islamic Azad University, 2017)
Waterpipe Tobacco Smoke(WTS) is an unhealthy life style that may increase the risk of genotoxic responses and chronic diseases such as cancer. Micronucleus test is a successful and reliable method which is used for screening of genetotoxic responses of whole body and also for screening those people who had already exposed to genotoxic compounds. In this study, specific questionnaires were designed and used for studying the role of shisha smoking on the extent of genotoxic responses and cases were looked for MNs with this biomonitoring method. The study population was 20 young adults (12men and 8 women) who born and lived in Tehran and had continuously smoked shisha more than 2 times weekly for more than 2 years . The associations between all recorded background, environmental and nutritional factors and increased incidence of Micronucleus in buccal cells of all cases were considered by statistical methods. In order to count Micronucleus levels, buccal cells were collected from buccal mucosa of these people with small-headed toothbrush and was placed the head of tooth brush into buccal cell buffer, slides were prepared and cells were stained with Schiff's reagent and light green .Finally 1000 differentiated cells were recorded by optical microscope in each slide and the mean level of MN was determined for each volunteer . All steps were performed according to the buccal micronucleus cytome (BMCyt) assay protocol. Increased incidence of Micronucleus was associated with the extent of shisha smoking per week (p=0.021), alcohol consumption ( p=0.021) and BMI ( p=0.027). The other effective factor in the occurrence of Micronucleus was gender/sex ( p=0.011) but nutritional factors didn't change the level of Micronucleus in our cases. The relationship between other background and environmental factors were not significant too. It seems that long term consumption of shisha in both genders could increase the risk of genetic toxicity and occurrence of malignancies in human target cells.